(untitled) (Iter, 2022)
Thispaper, which constitutes an introduction to a seminar with the same ñame, is articulated in four parts: L- Reflections aloud, 2.- Alétheia, 3.- Veritas and verum, 4.- As conclusión. The first andfourth parts are a meditation, introductive and conclusive respectively, about the issue o f truth. They start from personal considerations and extend until they reach a general visión o f the issue as it is presented in present society. The second is a general look at the way o f sensing the truth in Greece, as the discovery o f self in its entirety. The third, a synthetic visión o f the way o f sensing it, in Rome, in relation to belief and confidence, with what is certain andpermanent. In both cases, we are dealing with a definition which perfectly fits the idiosyncrasy o f both peoples.